การศึกษารูปแบบการบริหารโครงการ 1 อำเภอ 1 ทุน - จิตระดับ สมพงษ์; เก้าเอี้ยน สุรศักดิ์; สุนันท์ลิกานนท์ นวพร; มาสันเทียะ จุฑาภรณ์ (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract This study aimed to 1) explore the tendency and prospective obstacles which will impact an administration of the third and fourth cohorts of the One District One Scholarship (ODOS) project from relevant stakeholders, and 2) study and develop an effective administration and management of the ODOS project. There are two sources of data; one is data searched from documents and another is from samples who participated in a group discussion and in-depth interview. Researchers collected data from scholars, parents, senior officials and officials from the Office of Secondary Educational Service Area and Office of Education Affairs in foreign countries, as well as former ODOS scholars. Qualitative data was analyzed using data reduction, content analysis, and inductive summary. The research findings were as follows: 1) The tendency and prospective obstacles which will affect the administration of the ODOS project consisted of insufficient preparation time, a lack of systematic verification of income criteria, educational degree certification, ineffective coordination on academic fields that locally required, and score comparison resulted in inconsistent evaluation of academic achievement. 2) The result of the study and development of an effective administration and management of the ODOS project indicated that the project’s philosophy, policy and objectives were significantly changeable upon the managerial politicians. The project committee could not provide different information or opinions which called for an adjustment of the committee’s administration from an individual-basis decision toward collective decision making. As an important project, it was suggested that ODOS should be recognized as a department, a juristic person which provided independency under the administration of the Permanent Secretary of the Ministry of Education.